Macphail’s Null Hypothesis of Vertebrate Intelligence: Insights From Avian Cognition - Bastos, Amalia P. M.; Taylor, Alex H. (Frontiers in Psychology, 2020)
Macphail famously criticised two foundational assumptions that underlie the evolutionary approach to comparative psychology: that there are differences in intelligence across species, and that intelligent behaviour in animals is based on more than associative learning. Here, we provide evidence from recent work in avian cognition that supports both these assumptions: intelligence across species varies, and animals can perform intelligent behaviours that are not guided solely by associative learning mechanisms. Finally, we reflect on the limitations of comparative psychology that led to Macphail’s claims and suggest strategies researchers can use to make more advances in the field.